Swiss Journalists' Role Performance: The relationship between conceptualized, narrated, and practiced roles. (26th April 2019) - Raemy, Patric; Beck, Daniel; Hellmueller, Lea
Abstract : Journalism scholars have mostly studied journalistic role conception and their manifestations in news separately. This study merges these two research approaches to suggest a holistic understanding of the relationship between role conception and role performance. The Swiss case offers a unique context for studying the relationship between ideals and practice because of comparatively weak economic and political pressures on journalism, thus leading to a strong connection between journalistic ideals and practice. This study combined a content analysis of 519 news articles—published in German, French, and Italian—with an online survey of 62 authors of these articles. The analysis reveals that Swiss journalists perceive several role conceptions as important and say they frequently perform these roles in their daily work. Although they claim to have rather high freedoms in reporting, journalists' conceptions of their role performance do not correspond to their actual role performance in news coverage. Factors that influence journalistic coverage are critically discussed to explain the relationship between role conception and role performance in a media system that offers high autonomy to journalists.